Mergers and Acquisitions of the Financial Institutions: Factors Affecting the Employee Turnover Intention - Baniya, Rojan; Adhikari, Sujan (NRB Economic Review, 2017)
A prudent analysis of the factors affecting turnover intention of the employees after mergers and acquisitions should guide the managers to prevent the fallout of employees during such complex process; the primary objective of this study is to identify those factors that influence turnover intention of the employees. Drawing from the previous studies, a conceptual framework was developed that took into account pre-merger organizational identification, procedural justice, utility with the merger, non-monetary benefits, monetary benefits, trust with merger and adequate authority delegation as variables that influence post-merger organizational identification and satisfaction with the merger. The results illustrate that pre-merger organization identification, utility with the merger, and trust with merger significantly predicted the post-merger organization identification, whereas only trust with merger significantly predicted the satisfaction with the merger. Furthermore, the study elucidates that the post-merger organizational identification could prevent the turnover intention among the employees. The findings of the study unravel sentiments of the employees during the consolidation process and provide the practitioners and the policy-makers with a base to develop an effective strategy to prevent turnover of employees during the mergers and acquisitions.